Filosofi Tradisi Ruwatan dalam Ritual Hindu Bali (Analisis Wayang Kulit Sudhamala dan Sapuhleger) - I Ketut Muada (Sanjiwani: Jurnal Filsafat, 2021)
The ritual of ruwatan in Balinese Hindu society basically removes or cleanses oneself from dirt, which is practiced almost the same in general throughout Bali. In ruwatan using wayang kulit media, there are two types of performing arts which contain the function and meaning of ruwatan, such as; puppet show gedog (weak puppet) and puppet show Peteng. The source of the pangruwatan play presented by the puppeteers refers to the ruwatan standard although in practice it changes according to the situation and conditions of the performance itself. The play taken in the wayang gedog is Sudhamala, while in the shadow puppet show at night it is Sapuhleger. Ruwatan or in Java known as murwakala has a broad meaning not only a literary work and pakeliran but its function and philosophy, it turns out that it refers to the micro and macro essence of humans as being creative, intellect and intention. This research specifically reveals problems regarding; the form of the play, the function and meaning of spiritual philosophy, as well as the role of government in relation to ritual rituals. In revealing this, the researchers used qualitative methods, as well as several theories that complement this research.